2021
DOI: 10.3390/ijms22137141
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nanoplastics (NPs) Increase the Toxicity of Metals in Fish Cell Lines

Abstract: Nanoplastics (NPs) are one of the most abundant environment-threatening nanomaterials on the market. The objective of this study was to determine in vitro if functionalized NPs are cytotoxic by themselves or increase the toxicity of metals. For that, we used 50 nm polystyrene nanoparticles with distinct surface functionalization (pristine, PS-Plain; carboxylic, PS-COOH; and amino PS-NH2) alone or combined with the metals arsenic (As) and methylmercury (MeHg), which possess an environmental risk to marine life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 69 publications
(107 reference statements)
1
14
0
3
Order By: Relevance
“…Therefore, lack of elevation in Bcl-2 expression while increase in BAX and Caspase-8 in cells treated with PS particles, indicate tipping of balance favoring apoptosis onset. Gonza ´lez-Ferna ´ndez et al had also observed increased transcription of BAX genes, concomitant with decreased gene expression of Bcl-2 in SaB-1 cells exposed to 50 nm aminated PS particle treatment compared to carboxyl or plain PS particles [74].…”
Section: Plos Onementioning
confidence: 93%
“…Therefore, lack of elevation in Bcl-2 expression while increase in BAX and Caspase-8 in cells treated with PS particles, indicate tipping of balance favoring apoptosis onset. Gonza ´lez-Ferna ´ndez et al had also observed increased transcription of BAX genes, concomitant with decreased gene expression of Bcl-2 in SaB-1 cells exposed to 50 nm aminated PS particle treatment compared to carboxyl or plain PS particles [74].…”
Section: Plos Onementioning
confidence: 93%
“…Commercial PS-NH 2 and PS-COOH displayed positive and negative charges, respectively, in ultrapure water. However, once resuspended in the culture medium, all the particles reduced their ζ-potential and showed a similar negative charge very close to the medium alone (−9.1 ± 1.0 mV) [29]. This charge reduction could be associated with the adsorption of proteins and lipids in the culture medium [31].…”
Section: Discussionmentioning
confidence: 87%
“…Clathrin-mediated endocytosis is also the primary route of internalization of virus into the cell [33]. Although we have not investigated the mechanism, we have reported that SaB-1 cells internalize NPs and suffer a strong and general stress state [29]. Therefore, the increased endocytic mechanism in cells leading to NP internalization might also contribute to increase the NNV attachment and entry, which has been suggested for GS cells [15].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations